2018
DOI: 10.1039/c8ee01136b
|View full text |Cite
|
Sign up to set email alerts
|

Fractional deviations in precursor stoichiometry dictate the properties, performance and stability of perovskite photovoltaic devices

Abstract: Reproducibility issues of perovskite materials and devices stem from their extreme sensitivity to fractional, quite possibly unintentional, deviations in the precursor solution stoichiometry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
222
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 141 publications
(249 citation statements)
references
References 76 publications
(152 reference statements)
20
222
4
Order By: Relevance
“…Not only are the perovskite thin‐film surfaces printed with 600–1100 dpi the most homogeneous, but for these layers the average composition of the surface also deviates less from the desired perovskite composition of Cs 0.1 MA 0.15 FA 0.75 Pb(I 0.85 Br 0.15 ) 3 . In this context it should be noted that for all element ratios a small lead deficiency is observed, which is in agreement to other XPS studies . Very thick (>1.5 µm) perovskite thin films processed with higher resolution (1400 and 2000 dpi) are significantly more inhomogeneous and contain significant excess of halides, cesium, and organic cations at the surface than the films deposited at lower resolution.…”
Section: Resultssupporting
confidence: 90%
“…Not only are the perovskite thin‐film surfaces printed with 600–1100 dpi the most homogeneous, but for these layers the average composition of the surface also deviates less from the desired perovskite composition of Cs 0.1 MA 0.15 FA 0.75 Pb(I 0.85 Br 0.15 ) 3 . In this context it should be noted that for all element ratios a small lead deficiency is observed, which is in agreement to other XPS studies . Very thick (>1.5 µm) perovskite thin films processed with higher resolution (1400 and 2000 dpi) are significantly more inhomogeneous and contain significant excess of halides, cesium, and organic cations at the surface than the films deposited at lower resolution.…”
Section: Resultssupporting
confidence: 90%
“…R exp ranging from 0.4 to 1.5 was observed to correlate proportionally to IE, showing that a perovskite film with excess PbI 2 film exhibits a higher IE, while perovskites with excess MAI show smaller IE. This similar trend can also be found by using one‐step solution method and varying the precursor ratios of a lead acetate trihydrate (Pb(Ac) 2 3H 2 O) and MAI . Furthermore, these trends in the energy levels variations are not only characteristic to MAPbI 3 but also to mixed halide perovskites of MAPb(I 1− x Br x ) 3 and MAPb(I 1− x Cl x ) 3 72e.…”
Section: Ensemble Averaged Properties Influencing Solar Cell Parameterssupporting
confidence: 73%
“…XPS is a widely employed surface science technique to investigate the surface chemical composition. A few systematic studies provide insights on the large variations in IE (ranging from 5.1 to 6.6 eV) and EA (3.9 to 4.6 eV) reported in literature 70,72c,e. Meerholz, Olthof, and co‐workers investigated the dependence of chemical composition (XPS) and corresponding energetics (UPS) by preparing 15 solution processed samples and 23 vapor deposited samples with various preparation conditions such as varying precursors molar ratios and annealing parameters 72c.…”
Section: Ensemble Averaged Properties Influencing Solar Cell Parametersmentioning
confidence: 99%
“…Since carriers can accumulate on these low‐bandgap regions, fractions of radiative recombination can be very high, and thus there is a large overall increase in the PL intensity . We note that unintentional fractional deviations in the precursor solution stoichiometry can also impact the extent and sign of photobrightening (or darkening) in perovskite films, a variable which would further contribute to the inconsistencies of reported results . It is reported that the PL intensity increases under continuous illumination in oxygen‐rich conditions even in multication perovskites such as (FA,MA,Cs)PbI 3 , but the extent and rate of this increase is in general lower compared to the MAPbI 3 analogues, suggesting there is at least to some degree a suppression of the photobrightening or photodarkening effects in those compositions .…”
Section: Sensitivity To Sample Morphology Composition and Passivationmentioning
confidence: 85%